Homilies on Psalms, 36-38 - Origen (Book collections on Project MUSE., 2023)
"Origen of Alexandria, Egypt (185-254 CE), an ancient Christian theologian and preacher, delivered homilies on the Psalms to his congregation in Caesarea, Palestine. Nine of these homilies, which are interpretations of Psalms 36, 37, and 38 (Psalms 37, 38, and 39 in modern numbering), were translated into Latin around the year 400 CE by the ancient Christian scholar Rufinus of Aquileia. This book is an English translation of Rufinus's Latin translation of these nine homilies, which originally had been composed and preached by Origen in Greek. These homilies of Origen offer primarily moral instruction to aid the souls of Christians in their progress toward knowledge of God. Included in this book is a scholarly introduction written by the translator, Prof. Michael Heintz of Mount Saint Mary's University (in Maryland)"--